Phrasal syntactic complexity measures in linguistics research articles written by Iraqi and English L1 writers - Alsahlanee, Ali; Paramaswari Jaganathan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Complex phrasal structures are considered the distinctive features in the academic writing of high-proficiency writers. The use of more complex phrasal structures increases the quality of the written text. Based on the contrastive rhetorical theory of writing, writers are required to use linguistic components in a specific way that meets the genre of writing. This study aims to investigate and compare the phrasal syntactic complexity measures of the texts of linguistics research articles written by Iraqi and English L1 writers. It identifies if there is a significant difference between the writing of Iraqi and English L1 writers in terms of using phrasal syntactic structures. This study utilised the corpus-based method to analyse linguistics research articles written by Iraqi and English L1 writers and published from 2016 to 2020. Twelve phrasal syntactic complexity measures were analysed by using the automatic analyser TAASSC. This study revealed a significant difference between the writing of Iraqi and English L1 writers in terms of the analysed phrasal complexity measures. Utilising the complex phrasal structures in Iraqi research articles would significantly contribute to the quality and publication acceptance in reputable international journals. This study is therefore significant to guide Iraqi researchers to improvise their academic writing skills for publication purposes.